Things Fall Apart in the Well of Lost Plots... Stories... Clues... Signs… Symbols... Meanings: A Philosophical Formalist Hermeneutic on Thomas Pynchon’s “The Crying of Lot 49” - Servaña, Alvin (Philosophy and Realistic Reflection, 2025)
Using Philosophical Formalism, I am executing a close textual examination of Thomas Pynchon’s “The Crying of Lot 49” as a “postmodern” novel. By looking into the implications of genre and/into the supposed self-aware critico-novelistic vision of Pynchon, I cascaded this critique as follows: Part 1: the semiotic/semiological texture of the novel; Part 2: the novel as a critical attempt to the Enlightenment-infused concepts in the contemporary time-space reality; Part 3: the novel as a psychedelic commentary on the modernist psychosis, thus a celebration and an interrogation of the legacies (?) of the intricacies or the lack thereof of the Postmodern cultural mood; for better or worse. What we can gleaned from this novel as a signifying practice of the Postmodern turn is something that is open to interpretations that I wish to consolidate and bring forth to the discourse—(con-)current to the issues that hover the Subject—elsewhere.